Experimental study of three in-line bubbles rising in still water by means of a three-dimensional (3D) shadowgraphy technique. Issue 1 (July 2021) - F Di, Nunno; Granata, F; Miozzi, M; Gargano, R; Marinis, G de; Pereira, F Alves; Felice, F Di
Abstract: The dynamics of rising bubbles in still water can be influenced by the wake characteristics of the neighbouring bubbles. An experimental study was conducted on individual rising bubbles rising in still water by means of volumetric shadowgraphy technique. Results highlighted a phase opposition relationship between the volumes and rising velocities and between the minor semi-axis and the two semi-axes median and major of the three air bubbles. The cross-correlation function applied on the eccentricities of the three bubbles highlighted similar positive peaks but also a negative peak between eccentricities of the second and third bubbles. Frequency spectra of the three bubbles eccentricities exhibited some common features, with peaks around 10 Hz for the first and third bubbles and around 5 Hz for the second and third bubbles. In addition, cross-correlation applied on the rising velocities showed negative correlations between the three bubbles, with each bubble that reduces its rising velocity while another accelerates. The application of the volumetric shadowgraphy allowed a simultaneous measurement of the geometry and rising velocities of the in-line bubbles, leading to identify common and different features among them.